Modeling of aircraft composite parts using simulation - Mat Desa, Wan Laailatul Hanim; Kamaruddin, Shahrul; Mohd Nawawi, Mohd Kamal (2012)
Simulation is one of the most powerful tools available for decision makers to study, analyze and evaluate any design and operation particularly for complex processes and systems. One of the largest application areas for simulation modelling is the manufacturing systems.As such, it is widely applied in manufacturing as a representation of the industrial operation systems allowing the systems to be observed, learnt and tested in a more holistic manner.This paper is based on a preliminary study that demonstrates the application of computer simulation modelling, which is a branch of Operations Research techniques, as a means to identify bottlenecks in order to determine the ideal operating conditions for large scale aircraft composite parts production plant in Malaysia.The model development of the plant under study was built using Arena software.